2012
DOI: 10.1371/journal.pone.0048694
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of the Very Low-Density Lipoprotein Receptor Mediates Lipid Accumulation in Clear-Cell Renal Cell Carcinoma

Abstract: Clear-cell renal cell carcinoma (RCC) is, in most cases, caused by loss of function of the tumor suppressor gene von Hippel–Lindau, resulting in constitutive activation of hypoxia-inducible factor (HIF)-1α and expression of hypoxia-induced genes in normoxic conditions. Clear-cell RCC cells are characterized histologically by accumulation of cholesterol, mainly in its ester form. The origin of the increased cholesterol remains unclear, but it is likely explained by an HIF-1α-driven imbalance between cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
46
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 22 publications
9
46
0
1
Order By: Relevance
“…Numerical values of mean concentrations and their standard deviations are listed in Table S4. Decreased levels of PE, SM and LPC in kidney tumor tissues in comparison with surrounding normal tissues are in agreement with previous reports [18,23].…”
Section: Quantitative Analysis Of Polar Lipid Classessupporting
confidence: 93%
See 1 more Smart Citation
“…Numerical values of mean concentrations and their standard deviations are listed in Table S4. Decreased levels of PE, SM and LPC in kidney tumor tissues in comparison with surrounding normal tissues are in agreement with previous reports [18,23].…”
Section: Quantitative Analysis Of Polar Lipid Classessupporting
confidence: 93%
“…Lipidomic analysis of RCC tissues and normal kidney tissues was performed using HPLC/MS [18], where significantly increased levels of cholesteryl esters (CE) and triacylglycerols (TG) and decreased levels of phosphatidylethanolamines (PE) and sphingomyelins (SM) in tumor tissues were reported. Mass spectrometry imaging using matrix-assisted laser desorption/ionization or desorption electrospray ionization was used for the relative comparison of tumor and surrounding normal tissues [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that HIF-1 directly binds to the promoter of the VLDL receptor (VLDLR). Furthermore, silencing of HIF-1α has been demonstrated to lead to a decrease in VLDLR and a subsequent decrease in LDL and VLDL uptake in response to hypoxia [160,161]. These effects of HIF-1 on VLDLR regulation help explain the higher levels of cholesterol observed in clear-cell RCC [161].…”
Section: Hypoxia-inducible Factorsmentioning
confidence: 99%
“…Furthermore, silencing of HIF-1α has been demonstrated to lead to a decrease in VLDLR and a subsequent decrease in LDL and VLDL uptake in response to hypoxia [160,161]. These effects of HIF-1 on VLDLR regulation help explain the higher levels of cholesterol observed in clear-cell RCC [161]. Lipoprotein receptor-related protein 1 (LRP1), which is also involved in the internalization of LDL, has also been shown to be a direct target of HIF-1 in vascular smooth muscle cells.…”
Section: Hypoxia-inducible Factorsmentioning
confidence: 99%
“…The tumor cells exhibit a characteristic histological feature of clear cytoplasm because of the large amount of lipid accumulation in the cytoplasm. 2 This lipid consists principally of cholesterol esters. Glycogenesis is also regulated by HIF-1α .…”
Section: Introductionmentioning
confidence: 99%